Comparison of entrepreneurial intentions among college students in China and Pakistan. (1st January 2013) - Ali, Shujat; Lu, Wei; Wang, Wenjun
In this comparative study, we conduct an empirical analysis on entrepreneurial intentions of college students in China and Pakistan based upon Shapero's entrepreneurial event model. Based on our empirical results, we suggest constructing a holistic policy with active cooperation from the government, industry and educational institutions in order to increase student exposure to entrepreneurship, along with teaching students the requisite knowledge for starting a business and obtaining financial capital.